Lactobacilli-dominated cervical microbiota in women with preterm prelabor rupture of membranes - Kacerovsky, Marian; Pliskova, Lenka; Bolehovska, Radka; Gerychova, Romana; Janku, Petr; Matlak, Petr; Simetka, Ondrej; Faist, Tomas; Mls, Jan; Vescicik, Petr; Zemlickova, Helena; Jacobsson, Bo; et al. (Pediatric research, 2020)
BACKGROUND: To determine the association between microbial invasion of the amniotic cavity (MIAC) and the presence of Lactobacillus crispatus- or Lactobacillus iners-dominated cervical microbiota in pregnancies with preterm prelabor rupture of membrane. Next, to assess the relationship between the presence of L. crispatus- or L. iners-dominated cervical microbiota and short-term neonatal morbidity. METHOD: A total of 311 women were included. Cervical samples were obtained using a Dacron polyester swab and amniotic fluid samples were obtained by transabdominal amniocentesis. Bacterial DNA, L. crispatus, and L. iners in the cervical samples were assessed by PCR. Cervical microbiota was assigned as L. crispatus- or L. iners-dominated when the relative abundance of L. crispatus or L. iners was ≥50% of the whole cervical microbiota, respectively. RESULTS: Women with MIAC showed a lower rate of L. crispatus-dominated cervical microbiota (21% vs. 39%; p = 0.003) than those without MIAC. Lactobacillus crispatus-dominated cervical microbiota was associated with a lower rate of early-onset sepsis (0% vs. 5%; p = 0.02). CONCLUSIONS: The presence of L. crispatus-dominated cervical microbiota in women with preterm prelabor rupture of membrane was associated with a lower risk of intra-amniotic complications and subsequent development of early-onset sepsis of newborns.
Keywords: Female; předčasná porodní činnost; Lactobacillus; novorozenec; cervix uteri; Ureaplasma; předčasný odtok plodové vody; Chlamydia trachomatis; Retrospective Studies; retrospektivní studie; Humans; Fetal Membranes, Premature Rupture; Amniocentesis; Obstetric Labor, Premature; těhotenství; Cervix Uteri; lidé; Mycoplasma hominis; amniocentéza; mikrobiota; Lactobacillus crispatus; Amniotic Fluid; plodová voda; ženské pohlaví; Microbiota; Pregnancy; chorioamnionitida; Infant, Newborn; Chorioamnionitis